Upper Bounds on the Degeneracy of the Ground State in Quantum Field Models - Asao Arai; Daiju Funakawa (Advances in Mathematical Physics)
Axiomatic abstract formulations are presented to derive upper bounds on the degeneracy of the ground state in quantum field models including massless ones. In particular, given is a sufficient condition under which the degeneracy of the ground state of the perturbed Hamiltonian is less than or equal to the degeneracy of the ground state of the unperturbed one. Applications of the abstract theory to models in quantum field theory are outlined.